(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2016)
يتميز التداول الإلكتروني لوثيقة الشحن البحري الإلكترونيّة بتفعيله مبدأ النظائر الوظيفية المنصوص عليه في قانون الأنوسيترال النموذجي للتجارة الإلكترونية إلا أنه يبرز عدداً من الإشكاليات التي تتمحور حول الإثبات بالدرجة الأولى ، وأخرى تتعلق بإيجاد قواعد تكميلية تحكم المؤسسات القانونية التي استحدثتها النصوص المختلفة المنظمة لمراحل التداول الإلكتروني ومن ثم تبناها قانون التجارة البحرية السوري مما وسّع السلطة التفسيرية لمحاكم الموضوع والقانون الناظرة في النزاع لاستحداث النظريات الأمثل في الإثبات لجهة تطويع مؤسسات الإثبات التقليدية المنصوص عليها في قانون البينات مع متطلبات الإثبات الإلكتروني والنظائر الوظيفية المستخدمة فيه في ظل حداثة تجربة التجارة الإلكترونية ، كما توسعت السلطة التقديرية لتمييز العناصر المكونة للمؤسسات القانونية المستحدثة في التداول الإلكتروني عن ما سواها في المستندات الإلكترونية الغير قابلة للتداول بغية إيجاد القواعد القانونية التي تحكم الالتزامات الناجمة عن هذا الأسلوب في التداول والتي تركت النصوص في كثير من المواطن للمحكمة تقدير حدود وآثار هذه الالتزامات مما أنشأ ضرورة البحث في حدود هذه السلطة ومرجعياتها القانونية . Transferring of electronic transport records is characterized by activating its functional equivalent provided by UNCITRAL model law on electronic commerce, but some issues may appear related to the burden of proof primarly and finding supplementary rules to govern legal institutions developed by the various rules which organize the electronic transferring steps which was adopted by the Syrian Maritime trade law , which expanded the explanatory authority of the trial courts and courts of law hearing the cases to develop the optimum theories of proof by adapting classical institutions of proof provided by law of evidence to face electronic proof needs and its functional equivalents used with modern electronic commerce experience . Also the judicial discretion was expanded to distinguish the elements of legal institutions developed in the electronic transferring from those in the non-negotiable electronic documents in order to find the legal rules which govern commitmentsarising from this way of transfer which left for the court the authority in many situations to evaluatethiscommitmentslimits and effects, so studying this authority limits and legal background was necessary .